RADON-222 ASSESSMENT AND ESTIMATION OF ANNUAL EFFECTIVE DOSE IN GROUNDWATER IN LAGOS STATE, NIGERIA. Issue 3 (28th February 2019) - Ademola, Janet Ayobami; Abdulkareem, Abdullateef
ABSTRACT: Radon-222 concentration in groundwater from Lagos State, Nigeria was measured. The arithmetic means of the radon concentration in the water ranged between 0.138 ± 0.058 and 0.411 ± 0.135 Bq.l −1 . The geometric means ranged from 0.121 to 0.389 Bq.l −1 . These were below the recommended limits set by International Organizations. The mean annual effective doses from the ingestion of radon-222 in water varied from 2.27 ± 0.95 to 6.75 ± 2.22 μSv.y −1 for adult, 4.54 ± 1.91 to 13.50 ± 4.43 μSv.y −1 for child and 2.65 ± 1.11 to 7.87 ± 2.58 μSv.y −1, for infant. The mean effective doses from ingestion for adults, children and infants are far less than the 0.1 mSv.y −1 recommended reference dose level from the intake of water for the period of a year. The mean annual effective dose from the inhalation of radon-222 ranged from 0.034 ± 0.014 to 0.101 ± 0.033 μSv.y −1 . The result of this study showed that the health burden due to the intake of radon-222 in the groundwater sampled is not significant.